Targeting conformational changes in C‐reactive protein to inhibit pro‐inflammatory actions - János G Filep (EMBO Molecular Medicine)
Abstract C‐reactive protein (CRP) is a marker of acute inflammation and modulator of host defense against infections. CRP exists in conformationally distinct forms that exhibit opposing biological functions and could amplify tissue damage. Therefore, therapies that efficiently target the deleterious actions of CRP are needed. In this issue of EMBO Molecular Medicine, Zeller et al report development of a novel low molecular weight phosphocholine‐mimetic that binds to pCRP and inhibits conformation change‐mediated expression of pro‐inflammatory actions without impairing its defense function and demonstrate its beneficial actions in preventing rejection of allograft transplants and renal ischemia–reperfusion injury.